Study on the antagonistic effects of koumiss on Toxoplasma gondii infection in mice - Yan, Xinlei; Sun, Yufei; Zhang, Guangzhi; Han, Wenying; Gao, Jialu; Yu, Xiuli; Jin, Xindong (Frontiers in Nutrition, 2022)
Toxoplasma gondii is an important food-borne zoonotic parasite, and approximately one-third of people worldwide are positive for T. gondii antibodies. To date, there are no specific drugs or vaccines against T. gondii. Therefore, developing a new safe and effective method has become a new trend in treating toxoplasmosis. Koumiss is rich in probiotics and many components that can alleviate the clinical symptoms of many diseases via the functional characteristics of koumiss and its regulation of intestinal flora. To investigate the antagonistic effect of koumiss on T. gondii infection, the model of acute and chronic T. gondii infection was established in this study. The survival rate, SHIRPA score, serum cytokine levels, brain cyst counts, β-amyloid deposition and intestinal flora changes were measured after koumiss feeding. The results showed that the clinical symptoms of mice were improved at 6 dpi and that the SHIRPA score decreased after koumiss feeding (P < 0.05). At the same time, the levels of IL-4, IFN-γ and TNF-α decreased (P < 0.001, P < 0.001, P < 0.01). There was no significant difference of survival rate between koumiss treatment and the other groups. Surprisingly, the results of chronic infection models showed that koumiss could significantly reduce the number of brain cysts in mice (P < 0.05), improve β-amyloid deposition in the hippocampus (P < 0.01) and decrease the levels of IFN-γ and TNF-α (P < 0.01, P < 0.05). Moreover, koumiss could influence the gut microbiota function in resisting T. gondii infection. In conclusion, koumiss had a significant effect on chronic T. gondii infection in mice and could improve the relevant indicators of acute T. gondii infection in mice. The research provides new evidence for the development of safe and effective anti-T. gondii methods, as well as a theoretical basis and data support for the use of probiotics against T. gondii infection and broadened thoughts for the development and utilization of koumiss.